CLIMATE CHANGE AND THE RISK MANAGEMENT IN SERBIAN INLAND WATERWAY TRANSPORT - Backalic, Todor; Maslaric, Marinko (Journal of Economic Development, Environment and People, 2012)
Climate changes require special attention and global monitoring. Impacts on nature and industry are increasingly evident. Water transport could be the backbone of the future European combined transport system. Unfortunately, risks in water transport are perhaps an under researched area and consequently, this article outlines a rationale, why it is necessary to develop competence about risk in water transport. The development of the cargo transport in river traffic depends directly on technical-exploitative characteristics of the network of inland waterways. Research of navigational abilities of inland waterways always comes before building ships or making a transport schedule. Navigation characteristics of rivers have to be determined as precise as possible, especially from the aspect of determination the possible draught of vessels. River transport due to their operational business and environmental conditions faced with several risks having different degrees of consequences. Current risk assessment methods for water transport just consider some dramatic events. We present a new method for the assessment of risk and vulnerability of water transport where river depth represents a crucial part. The analysis of water level changes on Serbian rivers during the last sixty years was done.